Unveiling microbiome signature in inner body fluids: comparison between wild and aquarium small-spotted catshark (Scyliorhinus canicula) - Muñoz-Baquero, Marta; Lorenzo-Rebenaque, Laura; García-Vázquez, Francisco Alberto; García-Párraga, Daniel; Martínez-Priego, Llucia; De Marco-Romero, Griselda; Galán-Vendrell, Inmaculada; D’Auria, Giuseppe; Marco-Jiménez, Francisco (Frontiers in Marine Science, 2023)
The microbiome is a crucial influencer in animal development, immune function and health, and it has complex and dynamic interactions with the environment, but little is known about the microbial signatures of inner body fluids. Recent evidence suggests that inner body fluids could be an indicator of the environmental interactions that fish experience. In the present study, we provide a comparative analysis of the microbial profile found in small-spotted catsharks’ blood plasma and seminal plasma and how microbial signatures vary between aquarium and wild animals. In the blood plasma microbiome, the habitat did not affect the α- and β-diversity, while in seminal plasma, both α- and β-diversity differed between both habitats. Proteobacteria are the main bacteria dominated independently the inner body fluid and habitats. No core microbiome was identified at the genus level, with only Pseudomonas and Cloacibacterium present in both inner body fluids and habitats. Of the 14 genera identified in blood plasma, only four were shared between habitats (making up 45.17% and 51.03% of relative abundance for wild and aquarium, respectively). Similarly, of the 100 genera identified in seminal plasma, only 41 were shared between habitats (84.79% and 64.83%, respectively). Moreover, in the seminal plasma, using ANCOM approaches, Serratia, Salinisphaera and Cutibacterium were found significantly enriched in aquarium animals. None potentially pathogenic bacteria were identified in the blood samples, while Coxiella, Prevotella, Coprococcus, Haemophilus and Phocoenobacter were potentially pathogenic bacteria identified in the seminal plasma samples. In summary, this study provides evidence of a circulating blood and seminal plasma microbiome in healthy small-spotted catsharks. Furthermore, dynamic changes were observed in the microbiome of these inner body fluids, which differed between the aquarium and wild habitats.